Hybrids of Methylxanthines and Azoderivatives as Acetylcholinesterase Inhibitors: Structure–Activity Relationship Analysis - Brunella Biscussi; Santiago Gundin; Martina Donozo; Ana Paula Murray (Chemistry Proceedings, 2024)
In this work, we synthesized methylxanthine and azobenzene derivatives, linked to secondary amines via a seven-carbon chain, to evaluate their acetylcholinesterase (AChE) inhibitory activity. Among the azobenzene compounds, 3a exhibited the highest activity with an IC50 of 1.1 µM. Meanwhile, the theobromine derivative 2a was the most potent inhibitor among the methylxanthines, with an IC50 of 0.19 µM. These results highlight the importance of structure–activity relationship analysis to optimize AChE inhibition by modifying pharmacophore fragments and secondary amines.